2021
DOI: 10.3390/cells10040744
|View full text |Cite
|
Sign up to set email alerts
|

Progressive and Coordinated Mobilization of the Skeletal Muscle Niche throughout Tissue Repair Revealed by Single-Cell Proteomic Analysis

Abstract: Background: Skeletal muscle is one of the only mammalian tissues capable of rapid and efficient regeneration after trauma or in pathological conditions. Skeletal muscle regeneration is driven by the muscle satellite cells, the stem cell population in interaction with their niche. Upon injury, muscle fibers undergo necrosis and muscle stem cells activate, proliferate and fuse to form new myofibers. In addition to myogenic cell populations, interaction with other cell types such as inflammatory cells, mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…To complete our knowledge on niche restructuration in FSHD muscles, additional components including soluble factors (laminins, collagens, fibronectin, prostaglandin E2, oncostatin M, etc.) [ 54 , 55 ] need to be investigated. Our preliminary data indicate that most of the macrophages present in affected muscles were of the M2-type (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To complete our knowledge on niche restructuration in FSHD muscles, additional components including soluble factors (laminins, collagens, fibronectin, prostaglandin E2, oncostatin M, etc.) [ 54 , 55 ] need to be investigated. Our preliminary data indicate that most of the macrophages present in affected muscles were of the M2-type (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CyTOF does suffer from several limitations, including the reduced sensitivity of metal-isotope-tagged antibodies and the longer acquisition times needed when using TOF-MS instruments. However, with these limitations being identified, there is massive scope for advances in these areas that will contribute to increasing the research possibilities of CyTOF in the future of skeletal muscle research [158][159][160]. Recently, Porpiglia et al [161] used CyTOF to study muscle stem cells (MuSCs) in the aged phenotype and showed high CD47 expression levels, which might be associated with dysfunctional MuSCs, and an impaired regenerative capacity.…”
Section: Antibody-based Methodologymentioning
confidence: 99%
“…Of crucial importance for the swift regeneration of damaged muscle fibers are myogenic stem cells, which are represented by the satellite cell population that is located between the sarcolemma and basal lamina in adult skeletal muscles. Satellite cell and activated muscle precursor cell proteomics has recently been carried out to identify biomarkers of fiber damage [298] and muscle aging [299].…”
Section: The Proteome Of Specialized Cells and Structures Within Skel...mentioning
confidence: 99%